Study of Physical and Anthropocentric Relationship with the Performance of State Level Cricket Players - Chawre, Rakesh; Saxena, Vikas (Integrated Journal for Research in Arts and Humanities, 2024)
This review paper examines the relationship between physical fitness, anthropometric characteristics, and the performance of state-level cricket players. The paper synthesizes existing literature to highlight how these factors influence performance in various cricketing roles, such as batting, bowling, and fielding. The findings suggest that a combination of physical and psychological factors significantly contributes to a player’s success on the field. The review also discusses implications for training programs and future research directions. This review paper explores the relationship between physical fitness, anthropometric characteristics, and the performance of state-level cricket players. By synthesizing existing literature, the paper highlights how factors such as strength, endurance, flexibility, agility, height, body composition, and mental toughness influence performance in various cricket roles, including batting, bowling, and fielding. The findings indicate that an integrated approach, combining physical training and psychological preparation, is crucial for optimal performance. This review also discusses the implications for personalized training programs and identifies potential areas for future research to further enhance understanding of these relationships.